Chasing charge localization and chemical reactivity following photoionization in liquid water - Marsalek, Ondrej; Elles, Christopher G; Pieniazek, Piotr A; Pluhařová, Eva; VandeVondele, Joost; Bradforth, Stephen E; Jungwirth, Pavel (The Journal of chemical physics, 2011)
The ultrafast dynamics of the cationic hole formed in bulk liquid water following ionization is investigated by ab initio molecular dynamics simulations and an experimentally accessible signature is suggested that might be tracked by femtosecond pump-probe spectroscopy. This is one of the fastest fundamental processes occurring in radiation-induced chemistry in aqueous systems and biological tissue. However, unlike the excess electron formed in the same process, the nature and time evolution of the cationic hole has been hitherto little studied. Simulations show that an initially partially delocalized cationic hole localizes within ~30 fs after which proton transfer to a neighboring water molecule proceeds practically immediately, leading to the formation of the OH radical and the hydronium cation in a reaction which can be formally written as H(2)O(+) + H(2)O → OH + H(3)O(+). The exact amount of initial spin delocalization is, however, somewhat method dependent, being realistically described by approximate density functional theory methods corrected for the self-interaction error. Localization, and then the evolving separation of spin and charge, changes the electronic structure of the radical center. This is manifested in the spectrum of electronic excitations which is calculated for the ensemble of ab initio molecular dynamics trajectories using a quantum mechanics/molecular mechanics (QM∕MM) formalism applying the equation of motion coupled-clusters method to the radical core. A clear spectroscopic signature is predicted by the theoretical model: as the hole transforms into a hydroxyl radical, a transient electronic absorption in the visible shifts to the blue, growing toward the near ultraviolet. Experimental evidence for this primary radiation-induced process is sought using femtosecond photoionization of liquid water excited with two photons at 11 eV. Transient absorption measurements carried out with ~40 fs time resolution and broadband spectral probing across the near-UV and visible are presented and direct comparisons with the theoretical simulations are made. Within the sensitivity and time resolution of the current measurement, a matching spectral signature is not detected. This result is used to place an upper limit on the absorption strength and/or lifetime of the localized H(2)O(+) ((aq)) species.
Keywords: kinetika; Quantum Theory; Electrons; voda; kvantová teorie; Water; Molecular Dynamics Simulation; Photochemical Processes; spektrální analýza; fotochemické procesy; Molecular Conformation; absorpce; Absorption; molekulární konformace; Kinetics; simulace molekulární dynamiky; Spectrum Analysis; elektrony; Protons; protony